AIM2 Stimulation Impairs Reendothelialization and Promotes the Development of Atherosclerosis in Mice - Lüsebrink, Enzo; Goody, Philip Roger; Lahrmann, Catharina; Flender, Anna; Niepmann, Sven Thomas; Zietzer, Andreas; Schulz, Christian; Massberg, Steffen; Jansen, Felix; Nickenig, Georg; Zimmer, Sebastian; Krogmann, Alexander Otto (Frontiers in Cardiovascular Medicine, 2020)
Background: Atherosclerosis has been shown to result from chronic inflammation caused by constitutive activation of the pattern recognition receptors (PRR), which are principle effectors of the innate immune system. PRR are present in the endosome or on the cellular membrane and can sense the aberrant release of nucleic acids, which is often a sign of acute or chronic cellular damage. Absent in melanoma 2 (AIM2) is a PRR that is expressed by vascular cells and specializes in detecting cytoplasmic double-stranded DNA (dsDNA). Activation of AIM2 leads eventually to activation of the inflammasome, but the role of AIM2 in vascular disease and atherosclerosis has not been well studied. Therefore, in this study we took advantage of acute and chronic models of vascular injury to determine the biological role of AIM2 in atherogenesis. Methods and results: We were able to induce significant release of proinflammatory cytokines in mice through the intravenous injection of a synthetic ligand for AIM2, double-stranded poly dA:dT. This cytokine release was shown to impair reendothelialization of the carotid artery and increase the number of circulating endothelial microparticles (EMP) after acute denudation, compared to treatment with vehicle. We saw an increase in the production of reactive oxygen species in the aorta, the number of circulating EMP, and, most interestingly, atherosclerotic plaque formation in apolipoprotein E-deficient (ApoE-/-) mice when they received continual subcutaneous poly dA:dT, in contrast to vehicle-treated animals. Finally, treatment with poly dA:dT did not impair vascular reendothelialization in AIM2-/- mice compared to vehicle controls in the carotid artery injury model. Conclusion: Overall, our data suggest that AIM2, as a known regulator of the inflammasome, is an active participant in atherogenesis, and highlight the importance of fully understanding the pathological mechanisms involved. It seems to be worth of further exploration as a therapeutic target, and future studies focusing on the effects of AIM2 activation as well as its pharmacological inhibition may reveal promising new therapeutic concepts for the treatment of atherosclerosis.